Association of various weight-based doses of continuous albuterol on hospital length of stay. (4th May 2021) - Parlar-Chun, Raymond; Arnold, Kristen
Abstract: Introduction: Continuous albuterol is a mainstay in management of pediatric status asthmaticus. While the National Heart Lung and Blood Institute Asthma Guidelines suggest 0.5 mg/kg/h as the recommended dosage, there is a paucity of evidence comparing different weight-based rates on hospital outcomes. Methods: Patients requiring continuous albuterol for asthma exacerbation from January 2015 to December 2016 were identified using ICD codes. The concentration of albuterol (5 mg/h–20 mg/h) and the duration of treatment were used to determine total albuterol administration. After dividing by patient weight, average weight-based doses were divided into equal quintiles. Unadjusted and length of stay adjusted for age, initial asthma severity score, and administration of magnesium were compared among the quintiles. The same multivariate analysis was used for duration of continuous albuterol. Results: Five hundred thirty-three hospitalizations for asthma were identified of which 289 received continuous albuterol. Weight-based dosage quintiles ranged from lowest (0.07–0.29 mg/kg/h) to the highest (>0.76–3.2 mg/kg/h). Baseline characteristics were similar aside from age, race, and magnesium administration. There was no difference in adjusted length of stay or adjusted duration of continuous albuterol therapy among the five quintiles. Conclusion: No optimal weight-based dose of continuous albuterol was found. Further investigation is needed to see if lower amounts of continuous albuterol may be as efficacious as higher doses. This could improve cost of status asthmaticus management and limit the number of adverse events associated with high exposure to continuous albuterol.